Method Development of Nested Allele-Specific Multiplex Polymerase Chain Reaction (NASM-PCR) for the Irritable Bowel Syndrome (IBS)-related Gene Polymorphisms - Rosdi, Rasmaizatul Akma; Musa, Nurfadhlina; Zahari, Zalina; Zahri, Mohd Khairi; Alfatama, Mulham; Khoo, Boon Yin (Iraqi Journal of Science, 2023)
Polymorphisms in the genes of G-protein subunit beta 3 (GNB3); rs5443, tryptophan hydroxylase 1 (TPH1); rs211105 and rs4537731, tryptophan hydroxylase 2 (TPH2); rs4570625 and sodium voltage-gated channel alpha subunit 5 (SCN5A); rs1805124, have known to cause the abnormalities in the gastrointestinal tract that are implicated to irritable bowel syndrome (IBS) predisposition. Upfront genetic polymorphism genotyping in IBS-related gene polymorphisms will help to intervene and guide the decision-making in the management of IBS patients. This study aimed to develop a genotyping method to detect the respective polymorphisms using nested allele-specific multiplex polymerase chain reaction (NASM-PCR). A combination of nested and allele-specific multiplex PCR method was developed to determine the five single nucleotide polymorphisms (SNPs) mentioned. Annealing temperature, annealing and extension times, and the concentrations of MgCl2, primers, and DNA samples were optimized in the PCR. Sanger sequencing was performed to validate the genotyping results. NASM-PCR for IBS-related gene polymorphisms were successfully developed. DNA bands which correspond to the genes and SNPs have shown 100% homologous with the gene database. The developed method of NASM-PCR was reproducible and specific to be used for determining the respective polymorphisms of IBS. Notably, the described method can easily be integrated into other laboratories for population study or clinical use.